Dendritic cell vaccination with a toll-like receptor agonist derived from mycobacteria enhances anti-tumor immunity - Vo, Manh-Cuong (Oncotarget, 2015)
Dendritic cell (DC)-based vaccines are considered useful in cancer immunotherapy, and the interaction of DC and adjuvants is important in the design of the next generation vaccines. In this study, whether DC combined with Rv2299c derived from mycobacteria could improve anti-tumor immune responses in a colon cancer mouse model was evaluated. MC38 cell lines were injected subcutaneously to establish colon-cancer-bearing mice and the following four groups were evaluated: PBS control, tumor antigen (TA) loaded-DC, Rv2299c, and a combination of TA-loaded-DC and Rv2299c. The combination treatment with TA-loaded-DC and Rv2299c exhibited greater inhibition of tumor growth compared to other groups. These effects were associated with the reduction of suppressor cells, such as myeloid-derived suppressor cells and regulatory T cells, and the induction of effector cells, such as CD4(+) T cells and CD8(+) T cells, in spleen, and with the activation of cytotoxic T Lymphocytes and NK cells. These results suggest that TA-loaded-DC vaccination with Rv2299c derived from mycobacteria enhanced anti-tumor immunity in a mouse colon cancer model by inhibiting the generation of immune-suppressive cells and recovering numbers of effector cells, and demonstrated superior polarization of the Th1/Th2 balance in favor of the Th1 immune response.